PENGARUH SERVICE QUALITY DAN BRAND IMAGE BERBASIS ISO 9001:2008 TERHADAP KEPUASAN PASIEN PADA RSUD ARIFIN ACHMAD PEKANBARU - M. Fadhil '; Samsir '; Iwan Nauli Daulay (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2016)
The purpose of this research is to analyze the influence of service quality and brand image based on ISO 9001: 2008 to patients satisfaction at RSUD Arifin Achmad Pekanbaru. This research use simple random sampling method in selecting respondents. Data will be analyzed descriptively and statistically. The results of this research shows that service quality and brand image based on ISO 9001: 2008 significanly influence on patient satisfaction. It showed the value of R square 68,1%, while the other 31,9% is influenced by other variables.The research shows that service quality and brand image based on ISO 9001: 2008 have significant influence as simultan to patient satisfaction. While as partiality service quality based on ISO 9001: 2008 have significant influence on patient satisfaction but brand image based on ISO 9001: 2008 does not significantly influence patient satisfaction.Keyword: service quality, brand image, and satisfaction